Extraction and Analysis of Methadone in Exhaled Breath Condensate Using a Validated LC-UV Method - Khoubnasabjafari, Maryam; Ansarin, Khalil; Jouyban-Gharamaleki, Vahid; Panahi-Azar, Vahid; Shayanfar, Ali; Mohammadzadeh, Laya; Jouyban, Abolghasem (Journal of Pharmacy & Pharmaceutical Sciences, 2015)
Purpose. A combined microextraction and separation method is presented for the determination of methadone in exhaled breath condensate (EBC) which is a promising non-invasive biological component for monitoring drug concentrations. Methods. In this work, dispersive liquid–liquid microextraction (DLLME) and ultrasonic liquid–liquid microextraction (ULLME) procedure coupled with a validated liquid chromatography method were used for analysis of methadone in EBC collected using an in-house cold trap setup. The method has been validated according to the FDA guidelines using EBC-spiked samples and tested on a number of EBC samples collected from patients. Results. The best DLLME conditions involved the use of a disperser solvent of methanol (1 mL), extraction solvent of chloroform (200 mL), EBC sample pH of 10.0 and centrifugation at 6000 rpm for 5 minutes. The conditions for ULLME were 150 mL of chloroform and the samples were sonicated for 4 minutes. The method was validated over the concentration range of 0.5–10 mg/L-1 in EBC. Inter- and intra-day precision and accuracy were less than 5 % where the acceptable levels are less than 20%. Furthermore, the validated method was successfully applied for the determination of methadone in patients’ EBC samples. Conclusions. The outcomes indicate that the developed LC-UV combined with DLLME and/or ULLME extraction methods can be employed for the extraction and separation of methadone in EBC samples. This article is open to POST-PUBLICATION REVIEW. Registered readers (see “For Readers”) may comment by clicking on ABSTRACT on the issue’s contents page.